Jesus and Temple : Textual and Archaeological Explorations - Charlesworth, James H. (Book collections on Project MUSE., 2014)
The New Testament provides abundant evidence that Jesus frequented the temple; according to Acts, so did his followers after his death. But the Gospels also depict Jesus in conflict with temple authorities, and questions about his attitude to the temple swirl around what the Gospels label false accusations from his opponents and around the dramatic but inconsistent accounts of Jesus "cleansing" the temple. Jesus' attitude toward the temple is at the center of current historical Jesus research, yet those discussions are often not current with the latest archaeological and related findings regarding the temple and its history, architecture, liturgy, and function. James H. Charlesworth here gathers essays from world-renowned archaeologists and biblical scholars to address the current state of knowledge regarding the temple and to consider anew vital questions about its significance for Jesus, for his followers, and for New Testament readers today.